The impact of autonomy-supportive organizational environments on employees' emotions and creative performance: A self-determination theory perspective. - Lan Ye; Yanwei Li; Na Zhang (PLoS ONE)
The ongoing debate over whether positive or negative emotions foster creative performance remains a pivotal issue in understanding the interplay between emotions and creativity. Emerging research suggests that both positive and certain negative emotions, such as fear and guilt, can enhance creativity under specific conditions. Grounded in Self-Determination Theory (SDT), this study examines how autonomy-supportive organizational environments contribute to the satisfaction of employees' basic psychological needs. It further explores how these needs influence work-related emotions and ultimately foster creative performance. Data were collected from 283 leaders and employees across various enterprises in Mainland China. Descriptive statistics were analyzed using SPSS 26.0, and structural equation modeling (SEM) with latent variables was conducted using AMOS 26.0 to test the hypothesized relationships and mediating effects. The results demonstrate that autonomy support positively influences the satisfaction of basic psychological needs, which subsequently promotes positive emotions and enhances creative performance. Conversely, autonomy support negatively affects the frustration of basic psychological needs, thereby mitigating negative emotions. Mediation analyses reveal that basic psychological needs mediate the relationship between autonomy support and emotions, while both positive and negative emotions mediate the relationship between autonomy support and creative performance. These findings provide valuable insights into the mechanisms linking autonomy-supportive environments, psychological needs, emotions, and creativity. Beyond its theoretical contributions to SDT, this study offers practical guidance for organizations aiming to cultivate employee creativity and well-being by fostering supportive and autonomy-oriented workplace climates.